Efek Perlakuan Kombinatif Plasma Medis dan Ekstrak Daun Binahong Terhadap Penyembuhan Luka Fase Proliferasi Pada Mencit Diabetik - Wahyuningtyas, Eka Sakti; Nasruddin, N; Rahayu, Heni Setyowati Esti; Lutfiyati, Heni; Sikumbang, Isabella Meliawati; Nurani, Laela Hayu; Kartikadewi, Arum; Salsabila, Nia; Putri, Gela Setya Ayu; Kurniasiwi, Putri; Dewi, Devi Kemala (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Plasma medicine is a relatively new and multidisciplinary studyinvolving the study of plasma science, biomedicine, pharmacy, andother health sciences to utilizing plasma for medical therapy. Plasmais the fourth substance, after solids, liquids, and gases. Plasma canproduce biological molecules of Reactive Oxygen and NitrogenSpecies (RON) which, if controlled in the right dose, can bebeneficial for health. This animal study examines the effect ofcombinative treatment of medicine plasma and binahong leaf extracton proliferation phase wound healing in a diabetic test model. Thestudy used Balb mice 7-8 years old which were induced by STZ withacute wounds which were divided into 4 groups, namely the woundgroup of diabetic mice without treatment (C), the group of diabeticmice with the treatment of binahong leaf extract (B), the group ofcombined treatment wounds plasma jet (P) and the wound group ofdiabetic mice treated with a combination of plasma and, binahongleaf extract (PB). Binahong leaf extract concentration 1% in DMSOsolvent. The jet type medicine plasma treatment was carried outevery day from day 0 to day 6. Macroscopic observation of thewound was carried out every day from day 0 to day 7. On day 7 itappears that the size of the wound area for P is much smaller thanfor C, B, and PB. The size of area B and PB is relatively the same,but smaller than C. The results of this study indicate that thebinahong leaf extract tends to inhibit the performance of medicineplasma in accelerating the healing of the proliferation phase.